Seismic study of a widened and reconstructed long-span continuous steel truss bridge. Issue 2 (1st February 2021) - Xu, Yan; Zeng, Zeng; Wang, Zhen; Yan, Hai
Abstract: For those steel bridges built decades ago, widening and reconstruction is an alternative and effective strategy to improve their traffic capacity. Seismic study of a widened and reconstructed long-span continuous steel truss bridge is presented in this paper. The width and weight of the bridge deck is therefore significantly increased, but the pile foundations cannot be strengthened because of the construction restriction. As a main traffic line crossing Huangpu River in Shanghai, post-earthquake performance of uninterrupted service function and the lack of ductile components exclude the ductility seismic design of the bridge, therefore the seismic isolation design using friction pendulum bearings is an option. Key design parameters and the comprehensive isolation effects are studied to provide necessary technical supports for the seismic design of the widened and reconstructed bridge. Then, a notable pile cap vibration leading to an unfavourable seismic performance of the pile foundation is observed, and parametric analyses of the possible influence factors are further studied based on a simplified two-degree-of-freedom model of the bridge deck-pile cap interactive structure. On the basis of the achieved influence rules, design suggestions to improve the seismic performance of the pile foundation are proposed consequently.